Investigating Views of "Nativeness" of English Teachers in a Multilingual, Multicultural Setting - Al-Shammari, Sarah (2011)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Sarah Al-Shammari entitled, "Investigating Views of 'Nativeness' of English Teachers in a Multilingual, Multicultural Setting," June 2011. Available are both hard and soft copies of the thesis.